DIRECTIONS FOR THE DEVELOPMENT OF TRANSPORT MACHINES FOR OPEN-PIT MINING - Koptev, Vladimir; Kopteva, Alexandra; Ivanova, Tatiana (Journal of Applied Engineering Science, 2020)
The paper is devoted to the identification (in the form of an intermediate obtained result) of the main trends in the development of transport machines, their systematization, taking into account the current state of art, identification and assessment of the most significant trends in view of innovative prospects. The discussed technical solutions contribute to a significant modernization of transport systems of mining enterprises.